Kontribusi Komite Sekolah dalam Mengembangkan Budaya Sekolah Unggul Studi Situs pada SMK Negeri 1 Lamongan - Fathurrahman Fathurrahman; M. Saunan Al Faruq; Silvi Rosiva Rosdiana (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2026)
Abstract: The school committee played a strategic role in developing an excellent school culture through support, oversight, and the strengthening of collaboration among schools, parents, and the community. This is in releted with the view that a strong organizational culture emerges from the active involvement of stakeholders. Therefore, the school committee serves as one of the key pillars in promoting public participation to foster a school climate and culture that are oriented toward school excellence. This research aims to describe the contribution of school committees in developing superior schools. This research uses a qualitative approach with a case study method at SMK Negeri 1 Lamongan.. The selection of research informants was based on the strategic roles of the research subjects, including school committee members, the leadership of SMKN 1 Lamongan, teachers, and selected parents. Data were collected through observations of events and collaborative activities between the school committee and the principal, focusing on the phenomenon of collaboration among various stakeholders within the school. In addition, interviews were conducted with school committee members, the principal, and teachers, complemented by a review of relevant documents.Data analysis techniques are carried out through data condensation, display/presentation, verification and drawing conclusions. Data validity is carried out by data triangulation, source triangulation, member check, extension of observation time. The research results showed that the school committee made a significant contribution to improving the schools culture in the efective schools. Through: (1) establishing synergistic collaboration with the principal, school leaders, and teachers; (2) actively participating in school development team meetings related to school policies; (3) optimizing its role as a communicator of school programs to parents and the wider community; (4) conveying the aspirations of parents and the community to the school; (5) actively involving parents in school-based character-building and habituation activities; (6) supporting educational activities by assisting in committee fundraising efforts for learning programs. Keywords: School Committee Contribution, School Culture, Excellent School Abstrak: Komite sekolah memiliki peran strategis dalam mengembangkan budaya sekolah unggul, melalui dukungan, pengawasan, dan penguatan kerja sama antara sekolah, orang tua, serta masyarakat. Hal tersebut sejalan dengan pandangan bahwa budaya organisasi yang kuat lahir dari keterlibatan para pemangku kepentingan. Oleh karenanya komite sekolah menjadi salah satu pilar penting dalam menggerakkan partisipasi publik guna menumbuhkan iklim dan budaya sekolah yang berorientasi pada keunggulan sekolah. Penelitian ini bertujuan untuk menjabarkan kontribusi komite sekolah dalam mengembangkan budaya sekolah unggul. Penelitian didesain menggunakan penelitian kualitatif dengan jenis studi kasus pada SMK Negeri 1 Lamongan. Penentutan informan penelitian didasarkan pada peran strategis dari subjek penelitian meliputi anggota komite sekolah, pimpinan SMKN 1 Lamongan, dewan guru dan wali murid terpilih. Teknik pengumpulan data melalui observasi atas kejadian dan kerjasama komite dan kepala sekolah, melalui pengamatan fenomena kolaborasi antar elemen di sekolah. Wawancara dengan komite sekolah, kepala sekolah dan guru, serta dengan telaah dokumentasi. Teknik analisis data dilakukan melalui kondensasi data, display/penyajian, verifikasi dan penarikan kesimpulan. Keabsahan data dilakukan dengan trianggulasi data, trianggulasi sumber, member check, perpanjangan waktu pengamatan. Hasil penelitian didapatkan bahwasannya komite sekolah memberikan kontribusi signifikan dalam mengembangkan budaya sekolah unggul. Pada SMKN 1 Lqamongan , Melalui; 1) melaksanakan kerjasama sinergis dengan kepala sekolah, pimpinan sekolah dan guru; 2) dalam hal kebijakan sekolah, komite sekolah terlibat aktif dalam rapat tim pengembang sekolah; 3) mengoptimalkan peran menjadi komunikator program sekolah kepada wali murid dan masyarakat; 4) menyampaikan aspirasi wali murid dan masyarakat kepada pihak sekolah; 5) komite sekolah bersama wali murid aktif melibatkan dalam kegiatan pembiasaan baik di sekolah; 6) untuk penguatan kegiatan, komite sekolah membantu penggalangan dana komite untuk pembelajaran. Kata kunci: Kontribusi Komite sekolah, Budaya Sekolah, Sekolah Unggul